Flame-retardant waterproof high-density fiberboard and application thereof
By using modified inorganic fillers and adhesives of modified urea formaldehyde resin in fiberboards, the problem of insufficient flame retardancy and waterproofness of fiberboards is solved, and high-density and low formaldehyde release fiberboard preparation is achieved.
Patent Information
- Application Number
- CN202510178647.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-18
AI Technical Summary
Existing fiberboards have shortcomings in flame retardancy and waterproofness, and there are problems with formaldehyde release during production.
By adding modified inorganic filler and modified urea-formaldehyde resin to the wood fiber, the interface bond strength between the filler and the wood fiber is significantly enhanced, the flame retardancy and water resistance of the fiberboard are improved, and the formaldehyde emission is reduced.
The fiberboard has achieved high flame retardancy, high waterproofness and low formaldehyde emission, and overcomes the problems of uneven dispersion of fillers and deterioration of adhesive properties in the prior art.
Smart Images

Figure CN119795321A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiberboards, in particular to a flame-retardant and waterproof high-density fiberboard and application thereof. Background Art
[0002] Fiberboard is a man-made board made of wood fiber or other plant fiber, with urea-formaldehyde resin or other adhesives. Fiberboard has the advantages of uniform material, small difference in longitudinal and transverse strength, and not easy to crack. However, fiberboard is composed of organic combustibles and is a combustible material. It poses a great safety risk in residential fire protection. It also has poor water resistance and is easy to swell after absorbing moisture. It is easy to swell and deform in the humid climate in the south, affecting its use. In addition, urea-formaldehyde resin is mostly used as an adhesive in the production of fiberboard, which poses the hazard of formaldehyde release. In the prior art, a common method for improving the flame retardancy and water resistance of fiberboard is to add separate flame retardants such as phosphorus-based flame retardants, nitrogen-based flame retardants and water-resistant agents such as paraffin and silicone. However, most flame retardants have problems such as high flame retardant costs, toxicity of the flame retardants themselves or the gas fumes produced by the decomposition of the flame retardants during the flame retardant process, and when the amount added is too high, it is easy to have a significant negative impact on the performance and appearance of the board itself. When the amount added is too low, the flame retardant performance is difficult to achieve. Therefore, research and development has been conducted to add inorganic fillers such as calcium carbonate to fiberboards. The non-combustible nature of calcium carbonate itself is utilized to add it to the fiberboard to hinder the combustion of the fiberboard. Calcium carbonate will decompose endothermically at high temperatures to produce calcium oxide and carbon dioxide. The endothermic reaction process can lower the ambient temperature. The released carbon dioxide can also dilute the combustible gas and oxygen, thereby hindering the further spread of the fire. At the same time, the calcium carbonate inside the fiberboard will not cause pollution to the environment under natural conditions as the fiberboard degrades. However, in terms of production process, if the process of applying glue first and then adding powder is adopted, it is easy to cause uneven distribution of powder. However, if the powder is mixed with urea-formaldehyde resin first and then applied, it will affect the adhesive properties of urea-formaldehyde resin, thereby causing serious quality defects in the fiberboard. Currently, there are studies on the use of silane coupling agents to regulate the surface of powder and wood fiber, but it still has a certain impact on the adhesive properties of urea-formaldehyde resin, and the performance of the fiberboard has not been significantly improved. Summary of the invention
[0003] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a flame retardant and waterproof high-density fiberboard and its application. By adding an adhesive composed of modified inorganic filler and modified urea-formaldehyde resin to wood fiber, the interfacial bonding strength between the filler and the wood fiber is significantly enhanced, the flame retardancy and water resistance of the fiberboard are improved, and its formaldehyde emission is reduced. At the same time, it has the advantages of flame retardancy, high waterproofness, and low formaldehyde emission.
[0004] The object of the present invention is to provide a flame retardant and waterproof high-density fiberboard, which comprises the following components by weight: 100-200 parts of wood fiber, 15-30 parts of adhesive, and 1-3 parts of waterproofing agent, wherein the adhesive comprises 10-20 parts of modified urea-formaldehyde resin, 5-10 parts of modified inorganic filler, and 0.1-0.2 parts of ammonium chloride, wherein the modified inorganic filler is a polydopamine modified inorganic filler; and the preparation method of the modified urea-formaldehyde resin comprises the following steps:
[0005] S1. Place the formaldehyde solution in a reactor, stir and heat, adjust the pH to alkaline, slowly add the first batch of urea, and simultaneously add a branched phenyl phosphorus polyol, wherein the amount of the branched phenyl phosphorus polyol added is 3-5 mol% of formaldehyde, and heat to 40-50 ° C and stir the reaction for a period of time;
[0006] S2. Continue to control the pH of the system to be alkaline, slowly add 1,3-adamantanediamine, wherein the amount of 1,3-adamantanediamine added is 3-5 mol% of formaldehyde, heat to 70-90 ° C, and stir the reaction for a period of time;
[0007] S3. Adjust the pH of the reaction system to acidic, slowly add the second batch of urea, control the temperature at 80-90°C, and stir the reaction for a while;
[0008] S4. After the reaction is completed, adjust the pH to alkaline, cool to 40-50°C and add the third batch of urea, continue stirring and reacting for a period of time and then discharge the material.
[0009] Preferably, the branched phenyl phosphorus polyol is prepared by reacting phenylphosphonic acid dichloride with a multifunctional polyol in the presence of a catalyst and an acid binding agent to obtain a branched phenyl phosphorus polyol having a hydroxyl terminal.
[0010] Preferably, the multifunctional polyol is selected from at least one of glycerol, trimethylolpropane and pentaerythritol, the catalyst is 4-dimethylaminopyridine, and the acid binding agent is triethylamine.
[0011] Specifically, the 1,3-adamantanediamine can be commercially available or homemade; preferably, the preparation method of the 1,3-adamantanediamine is: at room temperature, adamantane and bromine water are mixed in a diphenyl ether solvent, iron powder is added as a catalyst, dibromoadamantane is obtained after reaction, and then urea and trifluoroacetic acid are added, and 1,3-adamantanediamine is obtained by reaction at 140-180°C.
[0012] Preferably, the preparation method of 1,3-adamantanediamine can also be: controlling the temperature at 0-10°C, mixing 1,3-adamantanedicarboxylic acid and dichloromethane, adding a catalyst, and dripping a chlorination agent; stirring and heating to 37-38°C, reacting for 4 hours to obtain 1,3-adamantanedicarboxylic acid chloride; controlling the temperature at 10-0°C, dripping 1,3-adamantanedicarboxylic acid chloride into 25% ammonia water, reacting for 1 hour, filtering, drying, and obtaining adamantane 1,3-dicarboxamide; controlling the temperature at 0-10°C, adding adamantane 1,3-dicarboxamide to a sodium hydroxide aqueous solution, adding a halogenation agent, heating to 40°C, stirring and reacting for 6 hours, extracting with dichloromethane, separating the aqueous phase, and concentrating the dichloromethane phase to obtain a white solid, namely 1,3-adamantanediamine.
[0013] Preferably, the molar ratio of the first batch of urea, the second batch of urea and the third batch of urea is 1:(0.6-0.8):(0.1-0.2).
[0014] Preferably, the molar ratio of formaldehyde to urea in the modified urea-formaldehyde resin is (0.9-1.2):1.
[0015] Preferably, the preparation method of the modified inorganic filler is: mixing the inorganic filler with ethanol to obtain an inorganic filler suspension, dissolving dopamine hydrochloride in deionized water, slowly adding it to the inorganic filler suspension, adding ammonium hydroxide solution, stirring and reacting at 30-40° C. for a period of time to obtain a polydopamine-modified inorganic filler. Under alkaline conditions, dopamine can self-polymerize on the surface of the inorganic filler to obtain a polydopamine-modified inorganic filler.
[0016] Preferably, the inorganic filler in the modified inorganic filler is at least one of calcium carbonate, aluminum hydroxide, silicon dioxide, diatomaceous earth, bentonite, magnesium hydroxide or talc, and the mass ratio of polydopamine to the inorganic filler is (1-1.5):100.
[0017] Preferably, the waterproofing agent is at least one of solid paraffin or emulsified paraffin.
[0018] Another object of the present invention is to provide a method for preparing the flame retardant and waterproof high-density fiberboard, comprising the following steps:
[0019] S1. The wood fiber is screened, impurities and metal hard objects are removed, and then placed in a cooking cylinder for softening, and then placed in a hot mill for hot grinding, and then mixed with a waterproofing agent in a mixer;
[0020] S2. The modified urea-formaldehyde resin, the modified inorganic filler and ammonium chloride are uniformly stirred to obtain an adhesive, the wood fiber is poured into a mixer, and the adhesive is evenly sprayed on the surface of the wood fiber with a spray gun during the stirring process. After the sizing is completed, the sizing fiber is dried to a moisture content of 5 to 8%;
[0021] S3. Weigh a certain mass of fibers for manual laying and pre-pressing, and finally put them into a hot press for hot pressing to obtain a high-density fiberboard.
[0022] Another object of the present invention is to protect the application of the flame retardant and waterproof high-density fiberboard in furniture manufacturing and interior decoration.
[0023] Beneficial Effects
[0024] The present invention provides a flame retardant and waterproof high-density fiberboard, which has the following beneficial effects by adding an adhesive composed of modified inorganic filler and modified urea-formaldehyde resin to wood fiber:
[0025] (1) Polydopamine has good adhesion properties and can form a uniform coating on the surface of inorganic fillers without significantly reducing the adhesive properties of urea-formaldehyde resin. Branched phenyl phosphorus polyols are added to urea-formaldehyde resin for modification. Branched phenyl phosphorus polyols have multiple terminal active groups, which can increase the reaction sites of formaldehyde, increase the content of branched polymers in urea-formaldehyde resin, and increase the cross-linking density of urea-formaldehyde resin, thereby enhancing the bonding properties of urea-formaldehyde resin. The addition of 1,3-adamantanediamine introduces adamantane structures with good heat resistance into the cross-linking network of urea-formaldehyde resin, further improving the stability and heat resistance of urea-formaldehyde resin, and can also consume free formaldehyde and reduce the formaldehyde release of fiberboard.
[0026] (2) The method of mixing the inorganic filler modified by polydopamine with the modified urea-formaldehyde resin before applying the glue can improve the dispersibility of the inorganic filler in the wood fiber, reduce the agglomeration phenomenon, significantly enhance the interfacial bonding strength between the inorganic filler and the wood fiber, and improve the flame retardant properties of the fiberboard. The modified urea-formaldehyde resin has better fluidity and permeability, and can better wrap and disperse the filler, further improving the dispersion effect of the filler. In addition, the introduction of branched phenyl phosphorus polyol and 1,3-adamantanediamine structure into the urea-formaldehyde resin improves the stability of the urea-formaldehyde resin, making the urea-formaldehyde resin flame retardant and heat resistant, thereby further improving the flame retardant properties of the fiberboard.
[0027] (3) The inorganic filler modified with polydopamine can form a dense barrier layer, significantly improving the barrier properties of the material and reducing the penetration of moisture and gas. The modified urea-formaldehyde resin has better water resistance and can further improve the barrier properties of the composite material, thereby improving the waterproof performance of the fiberboard. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the infrared spectrum of branched phenyl phosphorus polyol 1. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0031] The raw materials used in the embodiments and comparative examples are described below:
[0032] Wood fiber: eucalyptus fiber; moisture content 10%, Guangxi Fenglin Wood Industry Group Co., Ltd.
[0033] Inorganic filler 1: aluminum hydroxide, 99%, 1 μm, Guangzhou Nalong Chemical Co., Ltd.
[0034] Inorganic filler 2: heavy calcium carbonate, 200 mesh, Hezhou Qifeng Powder Co., Ltd.;
[0035] Waterproofing agent: solid paraffin, commercially available;
[0036] 1,3-adamantanediamine: Homemade, the preparation method is as follows: at room temperature, adamantane and bromine water are mixed in a diphenyl ether solvent, iron powder is added as a catalyst to obtain dibromoadamantane, urea and trifluoroacetic acid are added, and the reaction is carried out at 140-180°C for 1.5 hours, cooled, hydrochloric acid is added and stirred to dissolve the product, insoluble impurities are removed by filtration, the filtrate is neutralized by sodium hydroxide solution, and then an excess of organic solvent is added for extraction, the obtained extract is distilled under reduced pressure to remove the solvent, and vacuum dried to obtain 1,3-adamantanediamine.
[0037] Branched phenyl phosphorus polyol 1: homemade, the preparation method is as follows: 0.1 mol of 4-dimethylaminopyridine, 2 mol of triethylamine and 1.5 mol of pentaerythritol are dissolved in 80 g of dichloromethane, the reaction temperature is set to 45 ° C, 1 mol of dichloromethane solution of phenylphosphonyl dichloride is slowly dripped under nitrogen purge and stirring reflux, react for 24 hours, filter, wash the filtrate with distilled water three times, remove moisture with sodium sulfate, and vacuum dry to obtain the final product;
[0038] Branched phenyl phosphorus polyol 2: homemade, the preparation method is different from branched phenyl phosphorus polyol 1, the difference is that pentaerythritol is replaced by propylene glycol;
[0039] Linear phenyl phosphorus polyol: homemade, the preparation method is similar to branched phenyl phosphorus polyol 1, except that pentaerythritol is replaced by ethylene glycol;
[0040] The chemical structure of branched phenyl phosphorus polyol 1 was characterized by Fourier transform infrared spectroscopy (FT-IR, Nicolet 6700, Thermo Fisher Scientific, USA). Figure 1 As shown, the peaks of hydroxyl -OH, C=C bond on the benzene ring and P=O were detected simultaneously in the infrared spectrum of the product, proving the successful synthesis of the target product.
[0041] Modified inorganic filler 1: Homemade, the preparation method is as follows: 100g of inorganic filler 1 and 1000ml of ethanol are stirred and mixed at 30°C for 30min, 1.5g of dopamine hydrochloride is weighed and dissolved in 30mL of deionized water, the dopamine hydrochloride solution is slowly added to the suspension of inorganic filler 1, stirred for 30min, and then 9ml of 30% ammonium hydroxide solution is added, and the reaction is continuously stirred for 24h, filtered, washed with deionized water three times, and vacuum dried in an oven at 80°C to obtain a polydopamine modified inorganic filler.
[0042] Modified inorganic filler 2: homemade, the preparation method is similar to that of modified inorganic filler 1, except that inorganic filler 1 is replaced by inorganic filler 2;
[0043] Modified inorganic filler 3: Homemade, the preparation method is as follows: 100g of inorganic filler 1 and 1000ml of deionized water are stirred and mixed at 30°C for 30min, 1.5g of KH550 silane coupling agent is weighed and dissolved in 10v / v% ethanol aqueous solution, stirred for 30min, the inorganic filler 1 suspension is added to 80°C, the KH550 solution is added, the reaction is kept warm for 2 hours, and after filtration, the mixture is vacuum dried in an oven at 80°C to obtain KH550 modified inorganic filler.
[0044] Modified urea-formaldehyde resin 1: Homemade, the preparation method is as follows:
[0045] S1. Place a 37% formaldehyde aqueous solution in a reactor, stir and heat to 40°C, add sodium hydroxide solution to adjust the pH to 8.0-8.5, slowly add the first batch of urea, the total molar ratio of urea to formaldehyde is 1:1, the amount of the first batch of urea added is 50% of the total amount of urea added, dissolve the branched phenyl phosphorus polyol 1 in deionized water under slightly heated conditions, and then add it to the reactor system, the amount of branched phenyl phosphorus polyol 1 added is 3 mol% of the total mass of formaldehyde, heat to 40°C, and stir to react for 30 minutes;
[0046] S2. Control the pH of the system to 8.0-8.5, dissolve 1,3-adamantanediamine in deionized water and slowly add it to the reaction system. The amount of 1,3-adamantanediamine added is 3 mol% of the total mass of formaldehyde, and the temperature is raised to 70 ° C. The reaction is stirred for 2 hours;
[0047] S3. Add hydrochloric acid solution to adjust the pH of the reaction system to 4.5-5.5, slowly add the second batch of urea, the second batch of urea is added in an amount of 40% of the total amount of urea added, heat to 85 ° C, stir the reaction for 1 to 2 hours; determine the reaction endpoint by regularly measuring the viscosity of the solution;
[0048] S4. After the reaction is completed, the pH is adjusted to 8-8.5, the temperature is continued to be lowered and the third batch of urea is added. The amount of the third batch of urea added is 10 mol% of the total amount of urea added. After cooling to 40°C, the reaction is continued with stirring for 30 minutes, the pH is adjusted to 9, and the material is discharged.
[0049] Modified urea-formaldehyde resin 2: homemade, the preparation method is the same as that of Example 1, except that branched phenyl phosphorus polyol 1 is replaced by branched phenyl phosphorus polyol 2;
[0050] Modified urea-formaldehyde resin 3: homemade, the preparation method is compared with Example 1, the difference is that the addition amount of branched phenyl phosphorus polyol 1 is 5 mol% of the total mass of formaldehyde;
[0051] Modified urea-formaldehyde resin 4: homemade, the preparation method is the same as that of Example 1, except that the amount of 1,3-adamantanediamine added is 5 mol% of the total mass of formaldehyde;
[0052] Modified urea-formaldehyde resin 5: homemade, the preparation method is compared with Example 1, except that the amount of branched phenyl phosphorus polyol 1 added is 1 mol% of the total mass of formaldehyde;
[0053] Modified urea-formaldehyde resin 6: homemade, the preparation method is the same as that of Example 1, except that the amount of 1,3-adamantanediamine added is 1 mol% of the total mass of formaldehyde;
[0054] Modified urea-formaldehyde resin 7: homemade, the preparation method is the same as that of Example 1, except that the branched phenyl phosphorus polyol 1 is replaced by a linear phenyl phosphorus polyol;
[0055] Urea-formaldehyde resin: homemade, the preparation method is the same as that in Example 1, except that branched phenyl phosphorus polyol and 1,3-adamantanediamine are not added;
[0056] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0057] Embodiment 1 A flame retardant and waterproof high-density fiberboard, weight parts and preparation method are as follows:
[0058] 150 parts of wood fiber, 20.15 parts of adhesive, 2 parts of waterproofing agent, the adhesive includes 15 parts of modified urea-formaldehyde resin, 5 parts of modified inorganic filler, 0.15 parts of ammonium chloride, the modified urea-formaldehyde resin is modified urea-formaldehyde resin 1, and the modified inorganic filler is modified inorganic filler 1. The preparation method is as follows:
[0059] S1. The wood fiber is screened, impurities and metal hard objects are removed, and then placed in a cooking cylinder for softening. The cooking time is 8 minutes, the steam pressure is 0.8MPa, and then placed in a hot mill for hot grinding, and then mixed with a waterproofing agent in a mixer;
[0060] S2. The modified urea-formaldehyde resin, the curing agent and the modified inorganic filler are mixed and stirred to obtain an adhesive, the wood fiber is poured into a mixer, and the adhesive is evenly sprayed on the surface of the wood fiber with a spray gun during the stirring process. After the sizing is completed, the sizing fiber is dried to a moisture content of 5%;
[0061] S3. Weigh a certain mass of fibers for manual laying and pre-pressing, and finally put them into a hot press for hot pressing to obtain a high-density fiberboard. The pre-pressing pressure is controlled at 4 MPa, the hot pressing pressure is 18 MPa, the hot pressing temperature is 200°C, the hot pressing time is 6 min, and the obtained high-density fiberboard has a thickness of 12 mm.
[0062] Example 2
[0063] Compared with Example 1, the difference is that the modified urea-formaldehyde resin 1 is replaced by the modified urea-formaldehyde resin 2;
[0064] Example 3
[0065] Compared with Example 1, the difference is that the modified urea-formaldehyde resin 1 is replaced by the modified urea-formaldehyde resin 3;
[0066] Example 4
[0067] Compared with Example 1, the difference is that the modified urea-formaldehyde resin 1 is replaced by the modified urea-formaldehyde resin 4;
[0068] Example 5
[0069] Compared with Example 1, the difference is that the modified inorganic filler 1 is replaced by the modified inorganic filler 2;
[0070] Compared with Example 1, the difference is that the modified urea-formaldehyde resin 1 is replaced by the modified urea-formaldehyde resin 5; Comparative Example 2
[0071] Compared with Example 1, the difference is that the modified urea-formaldehyde resin 1 is replaced by the modified urea-formaldehyde resin 6; Comparative Example 3
[0072] Compared with Example 1, the difference is that the modified inorganic filler 1 is replaced by the modified inorganic filler 3; Comparative Example 4
[0073] Compared with Example 1, the difference is that the modified urea-formaldehyde resin 1 is replaced by the modified urea-formaldehyde resin 7; Comparative Example 5
[0074] Compared with Example 1, the difference is that the modified urea-formaldehyde resin 1 is replaced by urea-formaldehyde resin;
[0075] Comparative Example 6
[0076] Compared with Example 1, the difference is that no modified inorganic filler is added to the adhesive.
[0077] The adhesives and high-density fiberboards prepared in the examples and comparative examples were subjected to the following performance tests, and the results are shown in Table 1, respectively.
[0078] 1. Viscosity: Refer to GB / T 14074-2017 "Test methods for adhesives and resins for wood industry" and use NDJ-5S rotational viscometer to measure the viscosity of the adhesive. The temperature of the adhesive is maintained at 25°C. Each adhesive is measured three times, and the arithmetic mean of the three viscosities is taken as the test result;
[0079] 2. Free formaldehyde content: The free formaldehyde content of the adhesive is determined by hydrochloric acid titration. The specific process is as follows: Add 5g of adhesive, 35mL of distilled water and 15mL of anhydrous ethanol to a 250mL conical flask and mix well. After adding 8 drops of methyl red-methylene blue mixed indicator, neutralize with hydrochloric acid, and then quickly add 10mL of NH4C1 solution (mass fraction of 10%) and 10mL of sodium hydroxide solution (1mol / L), mix well, and let stand at room temperature for 30min. Neutralize with hydrochloric acid and record the volume of hydrochloric acid standard solution consumed. Set up a blank test without adding adhesive, and do not neutralize after adding the indicator. The rest of the steps are the same. Each adhesive is measured twice in parallel, and the arithmetic mean of the two measurement results is taken as the test result. The free formaldehyde content is calculated as follows:
[0080]
[0081] Wherein: F is the free formaldehyde content, expressed as a percentage (%); V1 is the volume of the hydrochloric acid standard solution consumed in the blank test, in milliliters (mL); V2 is the volume of the hydrochloric acid standard solution consumed in the titration sample, in milliliters (mL); c is the molar concentration of the hydrochloric acid standard solution, in moles per liter (mol / L); G is the mass of the adhesive, in grams (g).
[0082] 3. Static bending strength and elastic modulus: refer to GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels", use the three-point bending method for measurement, load evenly at a speed of 20mm / min on a MWW-10 universal mechanical testing machine, the specimen size is 300mm×50mm×12mm, and 2 specimens are taken from each fiberboard for measurement.
[0083] 4. Internal bonding strength: refer to GB / T 17657-2013 “Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels”, load evenly at a speed of 2mm / min on a MWW-10 universal mechanical testing machine, the specimen size is 50mm×50mm×12mm, and 5 specimens are taken from each fiberboard for measurement.
[0084] 5.24h water absorption thickness expansion rate: refer to GB / T 17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", immerse the specimen in a constant temperature water tank with a pH value of 7 and a temperature of 20°C, with the specimen surface perpendicular to the water surface and the upper part of the specimen 25mm below the water surface. Soak in water for 24 hours and measure the thickness change of the specimen before and after water absorption. The specimen size is 50mm×50mm×12mm, and 3 specimens are taken from each fiberboard. The calculation formula for the water absorption thickness expansion rate is as follows:
[0085]
[0086] Where: T is the water absorption thickness expansion rate, expressed as a percentage (%); t1 is the thickness of the specimen before immersion in water, in millimeters (mm); t2 is the thickness of the specimen after immersion in water, in millimeters (mm).
[0087] 6. Formaldehyde emission: Refer to GB / T17657-2013 "Test methods for physical and chemical properties of artificial boards and veneer artificial boards", and use the perforation extraction method for determination. The specimen size is 25mm×25mm×12mm. Take two 50g specimens to determine the moisture content, and take 110g of the specimen for extraction with toluene to obtain a formaldehyde aqueous solution. Then add the formaldehyde aqueous solution to a mixed solution of acetylacetone and ammonium acetate, heat it in a water tank at 60°C for 10 minutes, take it out and let it stand in a dark place for 60 minutes. Set up a blank test group. In the blank test group, deionized water is added to the mixed solution of acetylacetone and ammonium acetate, and the rest of the steps are the same. Use distilled water as the reference solution at 412nm on the ultraviolet spectrophotometer and adjust to zero. Use a cuvette to measure the absorbance of the extraction solution and the absorbance of the blank solution. The formaldehyde emission is calculated as follows:
[0088]
[0089] In the formula: E is the formaldehyde release, in milligrams per 100 g (mg / 100 g); A2 is the absorbance of the extract; A1 is the absorbance of the blank solution; f is the slope of the standard curve, in milligrams per milliliter (mg / mL); H is the moisture content of the specimen, expressed as a percentage (%); V is the volume of the volumetric flask, V=2000mL; m is the mass of the specimen in the extraction test, in grams (g).
[0090] 7. Cone calorimetry test: The test was carried out according to the procedure described in the Chinese national standard GB / T34749-2017. The sample size was 100 mm × 100 mm × 12 mm. The irradiance during the test was 50 kW·m -2 , the exhaust system flow rate is 0.024m 3 ·s -1 Before the test, place the sample in the middle of the aluminum foil and wrap its bottom and sides. When the temperature of the back-fire surface of the sample reaches 140°C, the test is terminated and the ignition time and continuous burning time are recorded. Take 3 specimens from each fiberboard for measurement.
[0091] Table 1 Performance test results of modified urea-formaldehyde resin
[0092]
[0093] It can be seen that adding branched phenyl phosphorus polyols and 1,3-adamantanediamine to urea-formaldehyde resin for modification can increase the cross-linking network density of urea-formaldehyde resin, consume formaldehyde, and effectively reduce the free amount of formaldehyde. When the modified urea-formaldehyde resin is modified by adding linear phenyl phosphorus polyols, the cross-linking density is insufficient, and the viscosity and solid content of the resin are poor.
[0094] Table 2 Performance test results of fiberboard
[0095]
[0096]
[0097] From the test results of the fiberboard, it can be seen that the high-density fiberboard prepared by the adhesive made by mixing modified urea-formaldehyde resin and modified inorganic filler has the effects of high strength, high modulus, flame retardancy, water resistance, and low formaldehyde release, overcoming the low adhesive performance and easy agglomeration caused by the addition of inorganic fillers in the prior art. The addition of branched phenyl phosphorus polyol and 1,3-adamantanediamine to urea-formaldehyde resin for modification not only increases the content of branched polymers in urea-formaldehyde resin, reduces its crystallinity, introduces flame retardant groups, and ensures adhesive performance and thermal stability, and has broad application prospects.
[0098] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A flame retardant and waterproof high-density fiberboard, characterized in that: The invention comprises the following components in parts by weight: 100-200 parts of wood fiber, 15-30 parts of adhesive, and 1-3 parts of waterproofing agent, wherein the adhesive comprises 10-20 parts of modified urea-formaldehyde resin, 5-10 parts of modified inorganic filler, and 0.1-0.2 parts of ammonium chloride, wherein the modified inorganic filler is a polydopamine modified inorganic filler; The preparation method of the modified urea-formaldehyde resin comprises the following steps: S1. Place the formaldehyde solution in a reactor, stir and heat, adjust the pH to alkaline, slowly add the first batch of urea, and simultaneously add a branched phenyl phosphorus polyol, wherein the amount of the branched phenyl phosphorus polyol added is 3-5 mol% of formaldehyde, and heat to 40-50 ° C and stir the reaction for a period of time; S2. Continue to control the pH of the system to be alkaline, slowly add 1,3-adamantanediamine, wherein the amount of 1,3-adamantanediamine added is 3-5 mol% of formaldehyde, heat to 70-90 ° C, and stir the reaction for a period of time; S3. Adjust the pH of the reaction system to acidic, slowly add the second batch of urea, control the temperature at 80-90°C, and stir the reaction for a while; S4. After the reaction is completed, adjust the pH to alkaline, cool to 40-50°C and add the third batch of urea, continue stirring and reacting for a period of time and then discharge the material.
2. The flame retardant and waterproof high-density fiberboard according to claim 1, characterized in that: The branched phenyl phosphorus polyol is prepared by reacting phenylphosphonyl dichloride with a multifunctional polyol under the action of a catalyst and an acid binding agent to obtain a branched phenyl phosphorus polyol with a hydroxyl group at the end.
3. The flame retardant and waterproof high-density fiberboard according to claim 2, characterized in that: The multifunctional polyol is selected from at least one of glycerol, trimethylolpropane and pentaerythritol, the catalyst is 4-dimethylaminopyridine, and the acid binding agent is triethylamine.
4. The flame retardant and waterproof high-density fiberboard according to claim 1, characterized in that: The preparation method of 1,3-adamantanediamine is as follows: at room temperature, adamantane and bromine water are mixed in a diphenyl ether solvent, iron powder is added as a catalyst, dibromoadamantane is obtained after reaction, and then urea and trifluoroacetic acid are added to react at 140-180° C. to obtain 1,3-adamantanediamine.
5. The flame retardant and waterproof high-density fiberboard according to claim 1, characterized in that: The molar ratio of the first batch of urea, the second batch of urea and the third batch of urea is 1:(0.6-0.8):(0.1-0.2).
6. The flame retardant and waterproof high-density fiberboard according to claim 1, characterized in that: The molar ratio of formaldehyde to urea in the modified urea-formaldehyde resin is (0.9-1.2):
1.
7. The flame retardant and waterproof high-density fiberboard according to claim 1, characterized in that: The preparation method of the modified inorganic filler is as follows: the inorganic filler and ethanol are stirred and mixed to obtain an inorganic filler suspension, dopamine hydrochloride is dissolved in deionized water, and slowly added to the inorganic filler suspension, and ammonium hydroxide solution is added, and stirred and reacted at 30-40° C. for a period of time to obtain the polydopamine modified inorganic filler.
8. The flame retardant and waterproof high-density fiberboard according to claim 1, characterized in that: The inorganic filler in the modified inorganic filler is at least one of calcium carbonate, aluminum hydroxide, silicon dioxide, diatomaceous earth, bentonite, magnesium hydroxide or talc, and the mass ratio of polydopamine to the inorganic filler is (1-1.5):
100.
9. The method for preparing the flame retardant and waterproof high-density fiberboard according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. The wood fiber is screened, impurities and metal hard objects are removed, and then placed in a cooking cylinder for softening, and then placed in a hot mill for hot grinding, and then mixed with a waterproofing agent in a mixer; S2. The modified urea-formaldehyde resin, the modified inorganic filler and ammonium chloride are uniformly stirred to obtain an adhesive, the wood fiber is poured into a mixer, and the adhesive is evenly sprayed on the surface of the wood fiber with a spray gun during the stirring process. After the sizing is completed, the sizing fiber is dried to a moisture content of 5 to 8%; S3. Weigh a certain mass of fibers for manual laying and pre-pressing, and finally put them into a hot press for hot pressing to obtain a high-density fiberboard.
10. Use of the flame retardant and waterproof high-density fiberboard according to any one of claims 1 to 8 in furniture manufacturing and interior decoration.
Citation Information
Patent Citations
Modified urea-formaldehyde resin adhesive used for high-dampness-proof fiber board
CN104830258A
Preparation method of composite modified adhesive and manufacturing method of anti-damp fiberboard
CN109096967A
Epoxy compound and polyol prepolymer modified urea resin and preparation method thereof
CN110615880A
Preparation method of flame-retardant waterproof urea-formaldehyde resin adhesive
CN112552849A
Flame-retardant PF adhesive, mechanically-enhanced OSB (oriented strand board) and preparation method of flame-retardant PF adhesive
CN117625099A
Cited By
High-density fiber wallboard and preparation method thereof
CN121853734A